Selectivity and efficacy of some herbicides in forest plant nurseries. - Del Busto, A.; Bimbo, B.; Garcia-Espana, V.; De Barreda, D. G. (CONGRESS 1997 - SOCIEDAD ESPANOLA DE MALHERBOLOGIA, PROCEEDINGS, 1997)
A experiment was conducted in a 4 especies of forest plants nurseries Quercus ilex L. Pinus halepensis Mill, Pinus pinea L. and Pistacia terebinthus L. with the following residual herbicides simazine, isoxaben, and thiazopyr. The treatment was done in preemergence of the weeds and the crops. Simazine, isoxaben and the mixture of both herbicides were selective in the four forest plants but thiazopir was phytotoxic.
The following values have no corresponding Zotero field: periodical: CONGRESS 1997 - SOCIEDAD ESPANOLA DE MALHERBOLOGIA, PROCEEDINGS pub-location: DEPARTAMENTO HORTOFRUTICULTURA , BOTANICA I JARDINERIA ETSEA, UNIVERSITAT LLEIDA, 25198 LLEIDA, SPAIN
Keywords: Herbicides; Pinus halepensis Mill; Pinus pinea L.; Pistacia terebinthus L.; plant nurseries; Quercus ilex L.; weeds control